2020
DOI: 10.1088/1755-1315/596/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Post-Harvest Practices Implemented by Fruit Farmers in Johor

Abstract: The post-harvest practice is important to maintain and prolong the shelf life of fruits and vegetable. However, farmer’s adoption towards agriculture practices is still low. This research aims to determine post-harvest adoption among fruit farmers in Johor. The study employs a Unified Theory of Acceptance and Use of Technology (UTAUT) and Theory Planned Behaviour (TPB) to evaluate the factors that influencing post-harvest practice adoption. 150 fruit farmers in Johor were chosen by using a simple random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study, Abu et al (2020) engaged a random sample of 150 fruit farmers in Johor and emphasised the need for post-harvest technology adoption to improve and maintain the quality of fruits. The study found that adopting post-harvest technology could help enhance fruits' per capita availability.…”
Section: Soil Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Abu et al (2020) engaged a random sample of 150 fruit farmers in Johor and emphasised the need for post-harvest technology adoption to improve and maintain the quality of fruits. The study found that adopting post-harvest technology could help enhance fruits' per capita availability.…”
Section: Soil Technologymentioning
confidence: 99%
“…In another study, Abu et al. (2020) engaged a random sample of 150 fruit farmers in Johor and emphasised the need for post-harvest technology adoption to improve and maintain the quality of fruits.…”
Section: Insights From the Literaturementioning
confidence: 99%